learning experience, quality assurance, student perception, alumni - Elena Casandra NIȚULESCU (Revista de Management Comparat International)
Team management is an essential concept, increasingly widespread, in order to form a united, performing and successful team that will be able to achieve the set goals. Managing a team means creating a balance between its needs and the needs of each team member, between the freedom that employees need to be creative and taking responsibility for their actions. Moreover, in our time, there is an increased emphasis on the operation of virtual teams at the most professional level. The article presents the vision approached in the literature on this subject and the institutional implications. All of this, with the corollary of the managerial approach from the perspectives of managing performance within teams, their delimitation from the group notion and the implications within an organization, are key points analyzed in the article, in correlation with a VUCA environment.